Diversity-Focused Undergraduate Premedical Enrichment Programs: The Impact of Research Experiences - Acevedo A; Babore YB; Greisz J; King S; Clark GS; DeLisser HM (Advances in Medical Education and Practice)
Ana Acevedo, Yonatan B Babore, Justin Greisz, Shakira King, Gabrielle S Clark, Horace M DeLisser Academic Programs Office, Perelman School of Medicine at the University of Pennsylvania, Philadelphia, PA, USACorrespondence: Horace M DeLisser, Academic Programs Office, Perelman School of Medicine at the University of Pennsylvania, Jordan Medical Education Center, 6th Floor, Building 421, 3400 Civic Center Blvd, Philadelphia, PA, 19104-5162, USA, Tel +1 215-898-4409, Fax +1 215-898-0833, Email delisser@pennmedicine.upenn.eduPurpose: Many diversity-focused, premedical enrichment programs anchor around a mentored research experience. Data, however, are lacking on how participation in mentored biomedical research in these program impacts participants’ subsequent medical student experience. To begin to address this gap, a cohort of first year medical students who had matriculated through a diversity-focused premedical enrichment programs was queried about the impact of their previous research experiences and their perceptions regarding medical school related research.Methods: This mixed methods study involved 10 first year medical students from groups underrepresented in medicine (URiM) who had matriculated to the Perelman School of Medical School of Medicine through the Penn Access Summer Scholars (PASS Program) and 10 non-URiM first year peers. At the start of medical school and after their first year, participants completed structured interviews and Likert style surveys to assess the impact of their pre-medical school research experiences and their current beliefs about the significance of research experiences to their medical education.Results: The quantitative analyses of the survey data demonstrated that the PASS and the non-PASS students were similar in their attitudes, beliefs, and assessments of their research competence. In contrast, qualitative analyses of the interviews offered a more nuanced picture of the differences and similarities between the two groups. The PASS students expressed more confidence in their research skills and felt better able to establish and maintain connections with mentors compared to their non-PASS peers. Both groups of students, however, expressed frustration at the lack of identity-concordant mentors to support their research aspirations and felt the pressure to do research to support their competitiveness for the residency match.Conclusion: The research experiences of diversity-focused enrichment programs may foster the agency and self-efficacy of participants in ways that support their success in medical school.Keywords: medical student diversity, diversity recruitment, pathway programs, health equity, health disparities, medical student admissions